Magnetocaloric effect in aluminum doped ErCr1−xAlxO3 orthochromites - Jolaikha Sultana; Asraf Sawon; Grace Brzykcy; Arjun K. Pathak; Sanjay R. Mishra (AIP Advances, 2024)
Aluminum-doped ErCr1-xAlxO3 orthochromites prepared via autocombustion technique were investigated for their magnetic and magnetocaloric properties. X-ray diffraction confirmed that samples were orthorhombic phases with the Pbnm space group without a trace of any impurity. As analyzed via Rietveld refinement of XRD data, structural parameters such as lattice parameters, volume, bond angle, and bond lengths were affected by doping nonmagnetic Al3+ in the compound. ErCrO3 possesses the long-range antiferromagnetic ordering with a weak display ferromagnetism at TN =133 K. Low-temperature high-field magnetic study shows a decrease in Neel temperature (TN ∼ 114 K for x = 0.5), suggesting magnetic ordering suppression due to Al3+ doping. The asymptotic paramagnetic Curie temperature Tcw = −25 K suggests the predominance of antiferromagnetic interactions in ErCrO3 orthochromites, which was observed to increase with Al3+ doping. Isothermal magnetization data show changes in magnetic entropy (−ΔSMmax) and relative cooling power (RCP). The magnetic entropy change, −ΔSMmax, for ErCrO3 estimated from magnetization measurements show 11.60 J kg−1 K−1 at 11 K and a relative cooling power (RCP) of 209.4 J kg−1 at 5 T applied field. While ErCr0.75Al0.25O3 show a maximum magnetic entropy of 11.52 J kg−1 K−1 at 11 K with a 5 T applied field and RCP of 186.66 J kg−1, whereas ErCr0.5Al0.5O3 displayed −ΔSMmax of 11.63 J kg−1 K−1 at 5 K with a 5 T applied field and RCP value of 160.78 J kg−1. The results show that nonmagnetic doping, such as Al3+, could maintain the compound’s magnetocaloric property to an extent.